Assessing Postoperative Recovery With Volatile Gas Versus Total Intravenous Anesthesia in Patients With and Without Obstructive Sleep Apnea. (June 2023) - Sagalow, Emily S.; Stewart, Matthew; Estephan, Leonard; Rodin, Julianna; Ananth, Ashwin; Curcio, Brian; Krein, Howard; Heffelfinger, Ryan; Thaler, Adam; Hunt, Patrick; Boon, Maurits; Huntley, Colin
Introduction: To determine if there is a recovery time difference between patients with and without obstructive sleep apnea (OSA) when using total intravenous anesthesia (TIVA) compared to volatile gas inhalational anesthesia. Patients and Methods: OSA and Non-OSA patients were identified at a tertiary institution between January 2019 and November 2020. Non-OSA patients were defined as those who have not been formerly diagnosed with OSA. A modified STOP-BANG score (MSBS) was performed to screen Non-OSA patients for OSA. Recovery was measured by Phase I recovery time, or time it took a patient to reach ≥9/10 on the Aldrete scoring system. Results: A total of 334 patients were included with 142 in the OSA cohort (59 TIVA, 83 inhalational anesthesia) and 192 in the Non-OSA cohort (119 TIVA, 73 inhalational anesthesia). In OSA patients, there was a 41.29-minute recovery time reduction when using TIVA versus sevoflurane ( P < .0001). Non-OSA patients recovered faster than OSA patients when undergoing inhalational anesthesia by 46.76 minutes and TIVA by 18.58 minutes ( P < .0001 and P = .0907, respectively). Non-OSA patients with a MSBS < 3 and ≥3 had a shorter recovery time compared to OSA patients when both underwent sevoflurane anesthesia (57.27 minutes, P < .0001 and 56.23 minutes, P = .040, respectively). Non-OSA patients with a MSBS of <3 had a decrease in recovery time of 26.68 minutes when compared to OSA patients who underwent TIVA ( P = .0004). Conclusions: When utilizing TIVA over inhalational anesthesia, patients with OSA have significantly increased benefit in terms of reduced Phase I recovery times as compared to Non-OSA patients.